Punished : a novel - Laestadius, Ann-Helén (Scribner Canada, 2025)
"When Else-Maj first arrives at school, she doesn't speak a word of Swedish and is terrified and confused. Her older siblings have warned her not to cross the Housemother. Dubbed The Witch by the children, Rita Olsson is brutal in her ways, quick to discipline the children with sadistic cruelty. At the school are also Jon-Ante, Marge, Nilsa, and Anne-Risten. They all have different ways of coping with their homesickness and the physical and psychological violence they endure. Little Jon-Ante has it worst, as he not only falls victim to Housemother's wrath, but also becomes the chosen punching bag of the older boys, with Nilsa as ringleader. The children have one solace: the nursemaid Anna who is always kind and quietly whispers in Sámi to them when Housemother doesn't hear. But when Anna oversteps her bounds in an effort to save an ill child, she is banished from the school. Back home, the children's parents are unaware of how their little ones are being treated, and those who try to speak up are met with silence and disbelief from the authorities. Some thirty years later, the five children have chosen different paths in order to survive -- or at least try to forget. Else-Maj is strong in her Sámi identity, but the trauma of her childhood has made her unable to connect emotionally with her own children, and she has turned to religion for comfort. Anne-Risten now only goes by Anne, cautiously hiding her heritage and speaking only Swedish to her little ones. Nilsa has become a reindeer herder like his father before him, but he continues to harbor an explosive anger -- and the violence to match. Jon-Ante has moved away and disconnected from the Sámi community because he cannot bear to face the tormenters of his youth, while his crooked pinky finger is a permanent reminder of Housemother's evil. And then there's Marge who has just adopted a six-year-old girl from another part of the world -- but she can't help questioning if it's right of her to uproot a child from their home and culture. Then suddenly, Housemother Rita reappears amongst them. Now an old, frail woman with God on her side, she has moved back into town. The five scarred children who are now grown up have neither forgotten nor forgiven her, and her reappearance ignites long-buried thoughts of revenge. Punished, the highly anticipated follow up novel to the runaway best-seller Stolen by Ann-Helén Laestadius, is a searing novel about trauma, memory, love, and loss, written in taut prose and vibrating with righteous rage. Told in alternate chapters cutting between the 1950's and 80's, and based on historical accounts of documented injustices, Punished exposes the Swedish state's greatest betrayal towards the Sámi: the nomad school system that shattered generations and caused loss of language, shame, and broken family ties."--